If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -13 = 71 Reorder the terms: -13 + 14x = 71 Solving -13 + 14x = 71 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 14x = 71 + 13 Combine like terms: -13 + 13 = 0 0 + 14x = 71 + 13 14x = 71 + 13 Combine like terms: 71 + 13 = 84 14x = 84 Divide each side by '14'. x = 6 Simplifying x = 6
| H=-4.9t^2+39.2t+1 | | P=2b^2+9b-5 | | -2+8(4n+5)=-34+8n | | 16+p=21 | | solve(x-1)(2x+3)(2x+5)(x+3)=945 | | X+7.4=-2.4 | | -24-4k=-7(k+3) | | 6x+2y+7z=46 | | b-21=8 | | 10X=9X+12 | | -(5+r)=3 | | 8y^2-32+24=0 | | 52x+2=212 | | 5x=4800 | | 2y-x-13=0 | | -19-7x=7(4x+7)+2 | | -15x^3-64+32x-4x^2+6=0 | | b-5(1-8b)=-5+3b | | -6y=3x+16 | | 45000=1382x+24963 | | 22x+42=17x+27 | | 7(-2)=5(x+2) | | 9(x+2)=18 | | -15x^3-(64-32x+4x)+6=0 | | -3(8+3b)=-2b+18 | | 6(3x-7)=21x | | 25x-58=8x+44 | | 2x+21=19 | | -2(4r+1)=-16+6r | | 67-3/4x=21 | | 9+17t-1=6t+34-2t | | 2x+33=75-5x |